Navigating English Literacy Challenges: A Qualitative Study of 12th-Grade Students Preparing for UTBK 2025 - Nabilah, Nada; Fitrianingsih, Fitrianingsih (Community Service Progress, 2024)
This study explores the English literacy challenges faced by 12th-grade students in Indonesia as they prepare for the UTBK 2025, focusing on reading comprehension, vocabulary, and grammar. Using a qualitative research approach, data were collected through semi-structured interviews, focus group discussions, and classroom observations from a purposively selected sample of 20-30 students. Thematic analysis revealed that the primary challenges students face include difficulties with complex academic texts, limited vocabulary knowledge, and grammatical errors, all of which hinder their performance in the English section of the UTBK. The study further investigates the factors influencing students’ English literacy preparation, such as the quality of educational support, access to external resources (e.g., online learning platforms, tutoring), and peer support. Results indicate that students attending well-resourced schools and those utilizing additional learning resources felt more prepared. Peer learning also played a key role in overcoming literacy challenges. Moreover, students employed various coping strategies, including active reading, vocabulary-building techniques, and practice tests, to improve their skills. This study provides valuable insights for educators and policymakers seeking to improve English literacy preparation for high-stakes exams like the UTBK.